Analisis Utilitas Biaya Pasien Dispepsia BPJS Dan Non-BPJS Kombinasi Obat Antasida Ranitidin dengan Antasida Lansoprazol - Aas Saadah; Prih Sarnianto; Hesti Utami R.; Irmin (LPPM Hang Tuah Pekanbaru, 2022)
Cost Utility is an analysis method of farmacoeconomy which compares the treatment cost with the patient’s life quality, dyspepsa is a relapse disease so it needs repetition medication which improve healthy cost and influence the patient’s life quality. This study is aimed to know the benefical of cost and the patient’s life quality which uses BPJS and Non BPJS from the combination of generic ranitidin antasida active substance with generic branded ranitidin antasida and generic lansoprazol antasida. This study was done as observational prospective during three months through structured interview at Insani Clinic with the 200 respondents which divided four groups, the respondent is the dyspesia patients which have visited medical history a dyspesia treatment at the clinic. Kruskal Wallis analysis was used to see differences in the quality of life of patients in the four groups, after which the Mann Whitney follow-up test and Cost Utility analysis were performed. The result of this study showed that based on Mann Withney test, it is obtained that there is difference of life quality toward four groups and cost utility analysis obtained from the comparison of generic medicine and generic branded wih the combination of antasida and ranitidin obtained is G1 about Rp 3.859 per QALYs with B1 about Rp 38.666 per QALYs with RIUB Rp 286.242, G2 about Rp 8.605 with B2 about Rp 68.788 with RIUB Rp 610.439, therefore it was obtained respondent is afford to pay more to get better life quality toward dyspesia disease at the clinic.